A conceptual framework for natural language steganalysis - Din, Roshidi; Samsudin, Azman (2011)
In order to have a viable steganalysis method, a steganalysis framework should be developed for natural language. Thus, this paper proposes a new definition of the steganalysis view in order to detect the hidden text used on natural language.This paper also analyzes and classifics several primitive components of natural language steganalysis domain. Primitive components such as resources and techniques of the natural language processing, steganography methods and steganalysis methods are presented in steganalysis environment. Thus, the integration of all these components can be known as a framework of natural language steganalysis which in return contribute to the e-application in security environment.